Hesperomyces (Fungi, Ascomycota) associated with Hyperaspis ladybirds (Coleoptera, Coccinellidae): Rethinking host specificity - Van Caenegem, Warre; Ceryngier, Piotr; Romanowski, Jerzy; Pfister, Donald H.; Haelewaters, Danny (Frontiers in Fungal Biology, 2023)
Laboulbeniales (Ascomycota, Laboulbeniomycetes) are biotrophic microfungi, always attached to the exoskeleton of arthropod hosts. They do not form hyphae or mycelium, instead they undergo determinate growth developing from a two-celled ascospore to form a multicellular thallus. Hesperomyces virescens has been reported on over 30 species of ladybirds (Coleoptera, Coccinellidae), but in reality it represents a complex of species, presumably segregating by host genus association. Here we report on Hesperomyces thalli on Hyperaspis vinciguerrae from the Canary Islands and compare them with He. hyperaspidis described on Hyperaspis sp. from Trinidad. We generated sequences of the internal transcribed spacer (ITS) region, the large subunit (LSU) ribosomal rRNA gene, and the minichromosome maintenance complex component 7 (MCM7) protein-coding gene. Our phylogenetic reconstruction of Hesperomyces based on a concatenated ITS–LSU–MCM7 dataset revealed Hesperomyces sp. ex Hy. vinciguerrae as a member of the He. virescens species complex distinct from He. virescens sensu stricto. It also revealed that Hesperomyces sp. ex Chilocorus bipustulatus from Algeria is different from He. virescens sensu stricto, associated with C. stigma from the USA. This suggests that species of Hesperomyces are not solely segregated by host, but that there is also a biogeographical component involved. Based on these data, we refrain from referring our material from Hy. vinciguerrae to He. hyperaspidis. Finally, we discuss the usefulness of MCM7 as a useful marker for species delimitation in Hesperomyces.